Modelling Open Social Scholarship Within the INKE Community. Issue 1 (27th February 2019) - Arbuckle, Alyssa; Maxwell, John
Given the current state of digital technology, there is a clear opportunity to revamp scholarly communication into a multi-faceted, open system that integrates and takes advantage of the near-ubiquitous global network. In doing so, the values of collaboration, sharing, and transparency inherent to open social scholarship can be integrated into knowledge dissemination methods. The Implementing New Knowledge Environments (INKE) community is currently organized around the idea of open social scholarship, but putting this into practice will involve assessing and revising INKE's own scholarly communication processes. In this paper, we explore the current state of open access to academic research and ruminate on next steps, beyond open access. We consider the role of collaboration in contemporary academic practice, and the importance of transparency in regards to multiplayer work. Further, we examine the standard scholarly communication model, especially as it pertains to INKE. Finally, we make recommendations and suggest alternatives for transforming our stock scholarly communication models into open social scholarship practices.